2018
DOI: 10.1515/ijamh-2018-0059
|View full text |Cite
|
Sign up to set email alerts
|

Determining the development of syntax in typically-developing Indian adolescents using a syntactic analysis package

Abstract: Background The syntactic structures used by adolescents can be calculated by measuring various markers that have the scope of developing with age. The use of such markers can be influenced by the type and modality of discourse on the individual uses. Aims The present study was aimed at exploring the syntactic development in 10–16-year-old Indian adolescents using markers such as sentences, clauses, subordinators, coordinators, T-units and the subordination index (SI) using written expository texts. Methods… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(5 citation statements)
references
References 19 publications
1
4
0
Order By: Relevance
“…The SLPs in the current study indicated the development of language to terminate either during childhood, adulthood, or later adulthood. Findings of studies on language development reveal language development to be an ongoing process that may actually never end (7)(8)(9)18) , which was also reported by a small proportion (24%) of participants in the current study. Contrastively, other research states language acquisition to begin during infancy, peaking during childhood, where there is maximum development of language due to supporting biological factors, and ending well before adolescence (19) .…”
Section: Adolescent Age Range and Later Language Developmentsupporting
confidence: 72%
See 4 more Smart Citations
“…The SLPs in the current study indicated the development of language to terminate either during childhood, adulthood, or later adulthood. Findings of studies on language development reveal language development to be an ongoing process that may actually never end (7)(8)(9)18) , which was also reported by a small proportion (24%) of participants in the current study. Contrastively, other research states language acquisition to begin during infancy, peaking during childhood, where there is maximum development of language due to supporting biological factors, and ending well before adolescence (19) .…”
Section: Adolescent Age Range and Later Language Developmentsupporting
confidence: 72%
“…Contrastively, New Zealand uses terms such as ‘youth’ and ‘adolescence’ synonymously, referring to ‘young people’ ranging between 10 and 24 years of age. Various researchers have studied adolescents who were considered to be aged between 10 and 24 years ( 16 ) , 13 and 19 years ( 17 ) , and 10 and 16 years ( 7 , 9 , 18 ) . Such a blend of use of adolescent periods does imply that it is conveniently decided and followed upon, with the precise onset and offset being difficult to be determined ( 1 ) , with no uniform pattern being recorded.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations